1994
DOI: 10.1115/1.2929453
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Tip Clearance Control for Centrifugal Compressor of an APU Engine

Abstract: To master today’s demand for efficiency and compactness of centrifugal compressor components for small gas turbine engines the main attention must not only be given to the aerodynamic design of the impeller and diffuser components, but also to the installation situation of the surrounding parts. A vital aspect is the tip clearance control between impeller and shroud casing over the total operating range. Using the radial compressor for a small gas turbine engine, developed at BMW Rolls-Royce, the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This diffuser ensures a wide flow range and is only applied for the initial tests that mainly deal with rotor flow. Typically, compressors of this kind are equipped with vaned diffusers having higher pressure recovery than vaneless diffusers (Japikse, 1992, Yoshinaka, 1994, Rodgers, 1982, Simon et al, 1986, Eisenlohr and Chladek, 1993. The vaneless diffuser will be replaced by a vaned type diffuser when the studies are extended to the whole stage.…”
Section: Test Compressor Andmentioning
confidence: 99%
“…This diffuser ensures a wide flow range and is only applied for the initial tests that mainly deal with rotor flow. Typically, compressors of this kind are equipped with vaned diffusers having higher pressure recovery than vaneless diffusers (Japikse, 1992, Yoshinaka, 1994, Rodgers, 1982, Simon et al, 1986, Eisenlohr and Chladek, 1993. The vaneless diffuser will be replaced by a vaned type diffuser when the studies are extended to the whole stage.…”
Section: Test Compressor Andmentioning
confidence: 99%
“…It has been universally long known that increasing the tip clearance decreases the compressor efficiency and pressure ratio. 1618 For example in a recent study, Hong and Abhari 19 got a slope of 0.37 for the efficiency drop due to the increasing tip clearance, meaning approximately one percentage point drop in efficiency for every three percentage point increase in the relative tip clearance. In a study of Turunen-Saaresti and Jaatinen 20 in which an array of studies was looked through, it was noted that the slope for the efficiency drop varied between 0.2 and 1.05 for different compressors.…”
Section: Introductionmentioning
confidence: 99%
“…Chriss et al 3 and Harthaway and Wood 4 emphasized the importance of throughflow wake, which is largely fed by the tip clearance flow when the centrifugal impeller is throttled. Eisenlohr and Chladek 5 described the possibilities for optimizing passive tip clearance control by design features and suggested that transient expansion processes must be considered when using a thermal tip clearance control.…”
Section: Introductionmentioning
confidence: 99%